Transferability of a previously validated imu system for lower extremity kinematics - Fain, A. C.; Hindle, B.; Andersen, J.; Nindl, B.; Bird, M.; Wills, J. A.; Doyle, T. (ISBS Proceedings Archive (Michigan), 2022)
This study tested transferability and validity of an Inertial Measurement Unit (IMU) system for estimation of lower limb kinematics. Peak hip, knee, and plantarflexion angles and sagittal plane range of motion (ROM) were compared during body weight squats (BWSQ) and countermovement jumps (CMJ) in 16 participants using root mean square error (RMSE) and intraclass correlation coefficients (ICC). RMSE was <15° for all but peak hip flexion in BWSQ and CMJ, and CMJ hip and ankle ROM. High ICC was observed in BWSQ knee ROM (0.927) and peak flexion (0.722), with moderate ICC in for peak hip flexion in BWSQ (0.469) and CMJ (0.595), and CMJ knee ROM (0.460). The IMU system produced acceptable lower limb kinematics in a novel environment. Future work will aim to minimize system-based differences and expand planes of motion.